Estimated dietary iodine intake as a predictor of placental size: evidence from the ELSPAC study - Bienertová-Vašků, Julie; Grulichová, Markéta; Mikeš, Ondřej; Zlámal, Filip; Pruša, Tomáš; Pohořalá, Aneta; Andrýsková, Lenka; Pikhart, Hynek (Nutrition & metabolism, 2018)
BACKGROUND: The relationship between low iodine status and pregnancy-associated comorbidities has been known for decades. The relationship between iodine intake and placental pathologies is, however, far less clear. This study was designed to examine the relationship between dietary iodine intake and placental size while also focusing on typical adverse pregnancy outcomes. METHOD: The dietary iodine intake of 4711 pregnant women enrolled in the Czech part of the European Longitudinal Study of Pregnancy and Childhood (ELSPAC) in 1990-1991 was established using a 145-item food frequency questionnaire. Multivariate linear regression models were used to estimate the relationship between dietary iodine intake during pregnancy and placental weight. Additional models were constructed to investigate the relationship between estimated dietary iodine intake and adverse birth outcomes. RESULTS: The estimated average iodine intake in the ELSPAC cohort was 106.6 μg/day. In the fully adjusted model, estimated dietary iodine intake was found to be significantly negatively associated with placental weight (β = -0.025, 95% CI: -0.044; -0.006, p = 0.011). Moreover, estimated dietary iodine intake was found to be significantly positively associated with the birth weight / placental weight ratio in the fully adjusted model (β = -0.024, 95% CI: 0.004; 0.043, p = 0.016). CONCLUSIONS: This study provides evidence of a relationship between estimated dietary iodine intake and placental weight and the birth weight / placental weight ratio. Additional research is warranted to provide more insight into the role of iodine in early as well as late placentation.
Keywords: Iodine intake; Placental weight; Birth weight / placental weight; ELSPAC; Birth outcome